Investigating different seed moisture at harvesting time on germination indices of corn varieties based on the standard and aging acceleration test conditions - koorosh rahbari; Mehdi Madandoost; farhad mohajeri; Mohamad Rahim Owji (علوم و فناوری بذر ایران, 2022)
The improper harvesting time can result in producing poor quality seed because leakage from the seed coat increases under these conditions. As such, it is critical to determine the proper seed moisture at the harvesting time. This study is included two years conducted in 2018 and 2019 as a factorial in the form of a randomized complete design under three replications. The first factor contains three corn varieties (Simon, AS71 and KSC703) whereas the second factor contains four harvesting times in terms of the seed moisture content (30, 35, 40 and 45%). The obtained results indicate that the highest electrical conductivity is observed in the early harvest treatment with 45% moisture, whereas the lowest electrical conductivity is observed in the treatment with 30% moisture at the harvesting time. The early harvest with 45% moisture decreases the viability as well as the percentage and germination rate of corn seeds. The highest viability of corn seeds at 35% moisture at the harvesting time is observed in AS71 varietie. Moreover, the germination of seeds of the Simon and KSC703 varieties did not reveal a statistically significant difference in the treatment of 30% moisture at the harvesting time with 35% and 40% moisture. The treatment with 45% moisture delayed the germination rate. In general, due to the reduction in the germination response at high moisture content at maturity time for standard and aging acceleration test, 30 and 35% moisture content at maturity time were found to be appropriate to produce high quality corn seeds.